Cold War, Personal Autonomy and Coherence of Self in the Theories of Communication: A Popular Culture Perspective - Mykkänen, Juri (Javnost-The Public, 2019)
The aim of this essay is to recognise similarities between Cold War Hollywood movies and major sources of the US communication theory. By analysing works by Erving Goffman, David Riesman and Paul Lazarsfeld from the 1940s and 1950s and films by Don Siegel and John Frankenheimer it is argued that both science and fiction shared a concern about potential fragility of the human self. Although the sources of fragmentation that were identified in these works were different, ranging from an extra-terrestrial life form and parent–child relationship to fundamentals of human interaction and dependence on others’ opinions, it appears that they all addressed the same problem of the constitution of the self. The films and academic works are situated in the Cold War context of the United States. The claim is made that they can be understood as reactions to Cold War anxieties and the generalised fear of cultural deterioration by uncontrollable forces. Occasionally these works use the theme of fragmented self as a form of social criticism besides making it a central element in social analysis.